Engineering a superwetting thin film nanofibrous composite membrane with excellent antifouling and self-cleaning properties to separate surfactant-stabilized oil-in-water emulsions - Tian, Miao (2021)
In recent years, novel superwetting membranes have gained popularity for oily wastewater treatments via synergy between surface chemistry and topography. However, the water fluxes of the superwetting membranes normally decrease rapidly due to pore clogging and surface fouling, especially when treating surfactant-stabilized oil-in-water emulsions. Herein, a facile strategy is proposed to develop a superwetting thin film nanofibrous composite (TFNC) membrane with remarkable antifouling and self-cleaning properties to effectively separate surfactant-stabilized oil-in-water emulsions. The membrane is composed of an ultrathin carbon nanotubes (CNTs)-polyvinyl alcohol (PVA) composite skin layer, and a highly porous electrospun nanofibrous substrate as well as a non-woven mechanical support. The robust three-dimensional (3D) CNTs composite skin layer were immobilized on the nanofibrous substrate surface by crosslinking the CNTs with PVA. This skin layer serves as a functional barrier to reject oil droplets, which exhibited excellent performance in treating surfactant-stabilized oil-in-water emulsions with a rejection of 95% and a competitive flux of ~60 Lm−2h−1 under an ultra-low pressure (20 kPa) in a cross-flow filtration process. Moreover, the CNTs composite layer also protects the membrane surface from fouling. The TFNC membrane possesses outstanding reusability, as the water flux could be recovered by 100% in a continuous cyclic operation without cleaning, which should be attributed to the underwater oil repellence of its superhydrophilic surface and self-cleaning property based on the capillary pumping effect occurred in the micron/nano-channels of the membrane surface.